Ground deformation and fault modeling of the 2016 sequence (24 Aug. – 30 Oct.) in central Apennines (Central Italy) - Pavlides, Spyros; Chatzipetros, Alexandros; Papathanasiou, George; Georgiadis, George; Sboras, Sotiris; Valkaniotis, Sotiris (Bulletin of the Geological Society of Greece, 2017)
A chain fault reactivation took place in central Apennines, from August 24 to October 30, 2016, producing five moderate-to-strong earthquakes ranging from Mw5.5 to Mw6.6. This paper presents the results from the study of the ground co-seismic ruptures around the Monte Vettore and Vettoretto, and Norcia. Surface co-seismic ruptures, were observed in the Vettore and Vettoretto segment of the fault for some kilometers (~7 km) in the August earthquakes, which were partly re-activated and expanded northward during the October earthquakes. Ruptures with 5-15 cm displacements are observed both in scree and weathered mantle (elluvium) and the bedrock, mainly fragmented carbonate rocks with small tectonic surfaces. After the October seismic sequence the co-seismic displacement doubled and reached more than 50cm. Oblique low-altitude aerial images were acquired at several sites using a UAV and 3D models were constructed using photogrammetric extrapolation. Numerous observed and mapped rock falls, slides of earth-materials etc, occur mainly along the mountain roads, on artificial slopes. They were studied with preliminary mapping from satellite imagery, and examples are presented of large landslides in the epicentral region with pre and after- the earthquake images. The first four events are associated with four individual fault segments respectively, all aligned along the mountain-fronts of Mt Gorzano and Mt Vettore. The last fifth and strongest event was the result of linkage and breaching of the previous fault segments. We modelled the fault segments into five seismogenic sources in order to calculate the post-sequence static stress changes produced by the five seismogenic sources (or source faults) to the surrounding faults (receiver faults). Our results suggest possible triggering effects for neighbouring faults located along the strike of the source faults and delay effects for faults which are directly located either on the footwall or hanging-wall.